Screening of Homoeopathic Formulation for the enhancement of Neurogenic Differentiation of Umbilical Cord derived Mesenchymal stem cells (UCMSCs) (Applied Biological Research, 2024)
Background: Mesenchymal stem cells are multipotent cells derived from various tissues, with the potential to differentiate into various cell types. They possess immunomodulatory properties and hold promise for therapeutic applications in neurodegenerative diseases and autoimmune disorders. Some homeopathic remedies, namely Plumbum metallicum (Plumb-met), Zincum metallicum (Zinc-met), and Agaricus muscarius (Agari-musc), are used to treat neuralgic pains and central nervous system disorders, However, the precise pathophysiological mechanisms underlying their actions remain unestablished. Aims & Objective: This study was aimed to investigate the efficacy of homoeopathic medicines Plumb-met, Zinc-met, and Agari-musc on Umblical cord derived mesenchymal stem cells (UCMSCs) and assess their cytotoxicity and their potential in neuronal differentiation. Methodology: UCMSCs were isolated and cultured. MTT assays were performed to evaluate the cytotoxicity of Plumb-met, Zinc-met, and Agari-musc at various potencies (6C, 12C, 30C, 200C, 1M) and concentrations (2%, 1%, 0.5%) over a 9-day induction period. Neuronal differentiation was induced, and the resulting neuronal cells were compared to a positive control. Observation: The MTT assay results revealed that the 6C potency of Plumb-met, Zinc-met, and Agari-musc was non-cytotoxic to UCMSCs. Notably, Zinc-met 6C, at concentrations of 1%, 0.5%, and 2%, exhibited a significant increase in the number of neuronal cells and extensive synapse formation. Plumb-met 6C and Agari-musc 6C also demonstrated neuronal differentiation and synapse formation, albeit to a lesser extent compared to Zinc-met in the 6C potency. Conclusion: This study indicated that Zinc-met (6C) has the potential to enhance neuronal differentiation in UCMSCs.
Keywords: Mesenchymal stem cells (MSCs); Ultra Higher Dilutions; Neurogenic Differentiation